2020
DOI: 10.3390/jpm10040165
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physician Experiences with Integrated Population-Scale Genetic Testing: A Mixed-Methods Assessment

Abstract: The scalable delivery of genomic medicine requires collaboration between genetics and non-genetics providers. Thus, it is essential to investigate and address the perceived value of and barriers to incorporating genetic testing into the clinical practice of primary care providers (PCPs). We used a mixed-methods approach of qualitative interviews and surveys to explore the experience of PCPs involved in the pilot DNA-10K population genetic testing program. Similar to previous research, PCPs reported low confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
(78 reference statements)
0
25
0
1
Order By: Relevance
“…For example, perceived understanding across result types was high overall; however, participants with lower education, lower income, or who did not identify as white reported feeling less confident in their comprehension and were more likely to indicate that they wanted additional resources to share results with family. In response to this finding, we are in the process of developing additional education materials for our program in multiple languages and making other program modifications to increase patient understanding and facilitate follow-up (Lemke et al , 2020 ). All patients are likely to benefit from the provision of resources that support patient education, family communication, and emotional responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, perceived understanding across result types was high overall; however, participants with lower education, lower income, or who did not identify as white reported feeling less confident in their comprehension and were more likely to indicate that they wanted additional resources to share results with family. In response to this finding, we are in the process of developing additional education materials for our program in multiple languages and making other program modifications to increase patient understanding and facilitate follow-up (Lemke et al , 2020 ). All patients are likely to benefit from the provision of resources that support patient education, family communication, and emotional responses.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that patients are getting appropriate follow-up care, clinical care pathways to systematically guide and monitor patient actions are being developed in the NorthShore EHR. In addition, we are piloting a genetic care coordinator role to assist patients and PCPs with appropriate medical management and to transition patients from primary to specialty care (Lemke et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying this evolving area of non-genetics provider practice, recent studies have evaluated the role of PCPs and non-genetics specialty providers in genomic medicine. Challenges in provider confidence and educational needs, and varying levels of perceived utility of genomic testing, have been identified by studies exploring the involvement of PCPs in genomic test implementation (37,46,54,75). However, a small number of studies have demonstrated that, while providers had various comfort levels with genomic testing and concerns about incorporating genomic sequencing into practice, most successfully provided appropriate clinical recommendations and planned to refer to genetics specialists when necessary (22,102).…”
Section: Incorporating Non-genetics Providersmentioning
confidence: 99%
“…There is increasing evidence that genomic screening may identify and improve outcomes for certain medically actionable conditions for which preventive measures and/or effective treatments are available [ 2 , 3 ]. Genomic screening programs, typically performed in the setting of large health system clinics [ 4 ], biobanks [ 2 ], or public health initiatives [ 3 ], may choose to return medically actionable findings with varying degrees of clinical utility. Recent studies have found that most individuals at genomic risk for medically actionable conditions are unaware of their risk [ 5 , 6 , 7 ], and that the majority of individuals informed of such risk will undergo recommended surveillance or risk-reducing interventions [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%